PENGARUH PEMBERIAN PROMOSI KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG PERKEMBANGAN MOTORIK HALUS PADA ANAK PRASEKOLAH USIA 3-5 - Umi Romayati Keswara; Dian Arif Wahyudi; Wiwik Erni Puspita Sari (Holistik Jurnal Kesehatan, 2019)
KNOWLEDGE, ATTITUDE AND ROLE OF HEALTH CARE PERSONNEL TOWARD APPLICATION OF HOUSEHOLD IN  HEALTHY‐LIFESTYLE BEHAVIORSBackground: Efforts to change people's behavior in order to support the improvement of health status are carried out through the Clean and Healthy Life Behavior Development Program. This program has been implemented by the Ministry of Health since 1996. One of the evaluations of the success is to look in healthy‐lifestyle behaviors indicators in the household setting. In Indonesia, the picture of health behavior that has not been good is shown by the proportion of household with good implemented by the Ministry of Health since 1996. One of the evaluations of the success is to look in healthy‐lifestyle behaviors, only 32.3%. implemented by the Ministry of Health since 1996. One of the evaluations of the success is to look in healthy‐lifestyle behaviors in Lampung Province in 2015 amounted to 59.2%. Pre-survey in Pujokerto Village for the implementation of healthy‐lifestyle behaviors in 2015 has not yet reached the target of the overall indicator.Purpose: Know the relationship of knowledge, attitudes and roles of health workers to the implementation of Household in healthy‐lifestyle behaviors in Pujokerto Village, Central Lampung Regency in 2017.Methods: Type of quantitative research, analytical design using aapproach cross-sectional. The population in this study were 124 of households. The number of samples of 95 household was taken by purposive sampling technique. Data analysis using chi-square.Results: The study showed that the frequency distribution of healthy‐lifestyle behaviors was mostly poor (58.95%), the frequency distribution of poor knowledge was 51.58% and p-value was 0.001, the frequency distribution of supportive attitude was 54.74% and p-value of 0.001 the frequency distribution of role of health care personnel supports 52.63% and p-value 0.004.Conclusion: A significant relationship between knowledge, attitudes and roles of health workers with the implementation of healthy‐lifestyle behaviors, suggests the need for sustainable health promotion activities to improve public knowledge about healthy‐lifestyle behaviors and change people's attitudes towards healthy‐lifestyle behaviors by using various media such as posters, banners and so on.Keywords: knowledge, attitude, role, health care personnel, household, healthy‐lifestyle behaviors Pendahuluan: Upaya untuk mengubah perilaku masyarakat agar mendukung peningkatan derajat kesehatan dilakukan melalui proram Pembinaan Perilaku Hidup Bersih dan Sehat (PHBS). Program ini telah dilaksanakan oleh Kementerian Kesehatan sejak tahun 1996. Salah satu evaluasi keberhasilan pembinaan PHBS dilakukan dengan melihat indikator PHBS di tatanan rumah tangga. Di Indonesia gambaran perilaku kesehatan yang belum baik ditunjukan dengan proporsi nasional RT dengan PHBS baik hanya 32,3%. Cakupan PHBS di Provinsi Lampung tahun 2015 sebesar 59,2%. Pra survei di Desa Pujokerto untuk pelaksanaan PHBS tahun 2015 belum mencapai target dari keseluruhan indikator.Tujuan: Diketahui hubungan pengetahuan, sikap dan peran tenaga kesehatan terhadap pelaksanaan PHBS Rumah Tangga di Desa Pujokerto Kabupaten Lampung Tengah Tahun 2017.Metode: Jenis penelitian kuantitatif, rancangan analitik menggunakan pendekatan cross-sectional. Populasi dalam penelitian ini adalah kepala keluarga berjumlah 124 kepala keluarga. Jumlah sampel 95 kepala keluarga diambil dengan tehnik purposive sampling. Analisa data menggunakan chi-square.Hasil: Pada penelitian menunjukkan distribusi frekuensi pelaksanaan PHBS sebagian besar kurang baik (58,95%), distribusi frekuensi pengetahuan kurang baik 51,58% dan p-value 0,001, distribusi frekuensi sikap mendukung sebanyak 54,74% dan p-value 0,001, distribusi frekuensi peran tenaga kesehatan mendukung sebanyak 52,63% dan p-value 0,004.Simpulan: hubungan yang signifikan antara pengetahuan, sikap dan peran tenaga kesehatan dengan pelaksanaan PHBS, saran perlunya kegiatan promosi kesehatan yang berkesinambungan guna meningkatkan pengetahuan masyarakat tentang PHBS dan merubah sikap masyarakat terhadap PHBS dengan menggunakan berbagai media seperti poster, spanduk dan sebagainya.